2005
DOI: 10.1016/j.cmet.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression of the human uncoupling protein 2 (hUCP2) to adult neurons extends life span in the fly

Abstract: The oxidative stress hypothesis of aging predicts that a reduction in the generation of mitochondrial reactive oxygen species (ROS) will decrease oxidative damage and extend life span. Increasing mitochondrial proton leak-dependent state 4 respiration by increasing mitochondrial uncoupling is an intervention postulated to decrease mitochondrial ROS production. When human UCP2 (hUCP2) is targeted to the mitochondria of adult fly neurons, we find an increase in state 4 respiration, a decrease in ROS production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
142
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 57 publications
11
142
2
Order By: Relevance
“…Furthermore, some, but not all, studies have indicated a role for IRS2 gene variants in the pathogenesis of obesity and obesity-associated insulin resistance (Sesti et al 2001;Stefan et al 2003). Indeed, we have recently found that subjects with one or two IRS2 Asp alleles displayed a greater chance of living between 96 and 104 years of age (Barbieri et al 2010) Recent experimental evidences suggest that the effect of the insulin IGF1 signaling pathway on life span may be partially mediated by regulating the expression of uncoupling protein 2 (UCP2) (Bratic and Trifunovic 2010;Andrews et al 2005) In flies, over-expressing human UCP2 (hUCP2) to adult neurons resulted in decreased oxidative damage and extended life span without compromising fertility or physical activity (Fridell et al 2005). Furthermore, a very recent study has demonstrated that the absence of UCP2 shortens life span in wild-type mice, and the level of UCP2 positively correlates with the postnatal survival of superoxide dismutase 2 mutant animals (Andrews and Horvath 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some, but not all, studies have indicated a role for IRS2 gene variants in the pathogenesis of obesity and obesity-associated insulin resistance (Sesti et al 2001;Stefan et al 2003). Indeed, we have recently found that subjects with one or two IRS2 Asp alleles displayed a greater chance of living between 96 and 104 years of age (Barbieri et al 2010) Recent experimental evidences suggest that the effect of the insulin IGF1 signaling pathway on life span may be partially mediated by regulating the expression of uncoupling protein 2 (UCP2) (Bratic and Trifunovic 2010;Andrews et al 2005) In flies, over-expressing human UCP2 (hUCP2) to adult neurons resulted in decreased oxidative damage and extended life span without compromising fertility or physical activity (Fridell et al 2005). Furthermore, a very recent study has demonstrated that the absence of UCP2 shortens life span in wild-type mice, and the level of UCP2 positively correlates with the postnatal survival of superoxide dismutase 2 mutant animals (Andrews and Horvath 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A role for UCP2 in regulating lifespan is strongly suggested by the ability of UCP2 to reduce ROS and regulate mitochondrial function in a diverse range of tissues (Fridell et al 2005;Andrews et al 2009) since mitochondrial dysfunction and ROS production lies at the heart of the aging process. In humans, some, but not all (Klannemark et al 1998), studies showed that UCP2 gene variants are implicated in diabetes, obesity, and fat metabolism (Zhang et al 2001) and are strongly linked to resting energy expenditure (Astrup et al 1999;Buemann et al 2001;Walder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of UCP2 on Erythroid Cell ROS-UCP2 expression in cardiomyocytes and neurons has been shown to alter the levels of ROS (12,13). We tested the levels of protein oxidation in isolated mitochondria and in whole cells from untreated bone marrow samples of UCP2 KO and WT (Fig.…”
Section: Ucp2 Function In Erythropoiesismentioning
confidence: 99%
“…The generation of ROS has been clearly established as a contributor to several neurodegenerative diseases and may underlie cellular changes seen in aging. Interestingly, targeted expression of UCP2 to the mitochondria of adult neurons can extend the life span in the fly by decreasing mitochondrial ROS production and attenuation of oxidative damage (51). We found that cells expressing hUCP4 exhibited reduced mitochondrial Ca 2ϩ uptake and ROS formation compared with control cells after store depletion with TG.…”
Section: Discussionmentioning
confidence: 59%